The Value of Immigrant Parents, The Power of Effective Adult Education: Fueling viable parent involvement through school-based adult ESL classes - Robin A. Waterman (Adult Education Research Conference, 2006)
This quasi-experimental study compares school-based adult ESL classes intentionally focused on parent involvement with those that are not. It addresses the need for empirical research of adult ESL instruction that integrates the most compelling goal of vast numbers of adult ESL students: supporting their children’s school success.
Keywords: Adult ESL; parent involvement